Tyrosine Phosphorylation of Botulinum Neurotoxin Protease Domains - Stephen eToth; Ernst E Brueggemann; George A Oyler; Leonard A Smith; Harry B. Hines; S. Ashraf eAhmed (Frontiers Media S.A., 2012)
Botulinum neurotoxins are most potent of all toxins. Their N-terminal light chain domain (Lc) translocates into peripheral cholinergic neurons to exert its endoproteolytic action leading to muscle paralysis. Therapeutic development against these toxins is a major challenge due to their in vitro and in vivo structural differences. Although three-dimensional structures and reaction mechanisms are very similar, the seven serotypes designated A through G vastly vary in their intracellular catalytic stability. To investigate if protein phosphorylation could account for this difference, we employed Src-catalyzed tyrosine phosphorylation of the Lc of six serotypes namely LcA, LcB, LcC1, LcD, LcE, and LcG. Very little phosphorylation was observed with LcD and LcE but LcA, LcB and LcG were maximally phosphorylated by Src. Phosphorylation of LcA, LcB, and LcG did not affect their secondary and tertiary structures and thermostability significantly. Phosphorylation of Y250 and Y251 made LcA resistant to autocatalysis and drastically reduced its kcat/Km for catalysis. A tyrosine residue present near the essential cysteine at the C-terminal tail of LcA, LcB and LcG was readily phosphorylated in vitro. Inclusion of a competitive inhibitor protected this Y426 of LcA from phosphorylation, shedding light on the role of the C-terminus in the enzyme's substrate or product binding.